A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 PEKANBARU IN READING COMPREHENSION - Yuliani, Rahmatika; Azhar, Fadly; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to find out what is the learning ability of the second-year students of SMAN 1 Pekanbaru in reading comprehension about descriptive texts, narrative texts, and recount texts. This is descriptive research. The numbers of sample are 72 students chosen by using cluster random sampling. Reading comprehension test were used to collect the data. The data were collected through 42 multiple choice reading test to measure students’ ability in comprehending descriptive, narrative, and recount texts. There were 8 components of reading that used: Factual Information (FI); Main Idea (MI); Guessing Vocabulary (V); Reference (R); Inference (I); Social Functions (SF); Generic Structure (GS); and Language Features (LF). The collected data were analyzed by using SPSS 26.0 and Microsoft Excel 2019. The result shows that the average score is 75.19 with 97.6 as the highest score and 30.9 as the lowest score. Thus, result indicates that the students’ comprehension is at good level.Key Words: Ability, Reading, Comprehension